The African sociopolitical crises of the 20th century in the cinema : Representations and reception - (:unkn) unknown (My University, 2021)
This thesis deals with some African socio-political crises of the 20th century, which Western producers and directors have brought to the cinema. The study, which is based on four films inspired by four serious crises, proposes to analyze respectively the relationship of historical truth to created fictional worlds, the reasons which pushed these agents of Western cinema to produce and direct films. on these crises, as well as the judgments issued by Western and African audiences in relation to these films in the corpus which are Lumumba, Hôtel Rwanda, Blood Diamond and Le Dernier Roi d’Ecosse. To effectively conduct such an analysis, the sociohistorical approach to cinema and the sociology of reception turn out to be the most relevant conceptual frameworks. Thus, the first part is concerned with the study of representations, that is to say, the way in which the various socio-political crises, examined in this research, are treated cinematically. The second part addresses the question of the life of films: the narrative options of producers and directors, the choices of actors and the assessments of critics and the public.
Keywords: African Research